DEMOCRACY AND EDUCATION ISLAM - Ulfa Masamah (Ta'dib: Jurnal Pendidikan Islam, 2015)
Education is one of the media that is Able to help develop the potential of all human beings. Over time the implementation of many educational experience problems when the role of education has a significant influence on improving the quality of human life. Islamic education as an agent of social change should be Able to hit the problem that move dynamically and proactively to the advancement and improvement of Muslims. Das sollen, the purpose of education in Islam as the process of formation of human beings to conform with the nature of existence. Therefore, we need an alternative thinking in an effort to minimize the various educational failure. Democratization of education Considered as a solution capable of Islamic education in creating a humanist. Education that does not justify the existence of intimidation, repression and restrictions on the creativity of teachers and students can be Realized with the Efforts to create a democracy marked by education teaching-learning process that is open and full of healthy and responsible dialogue between teacher and pupil. Humanist atmosphere in education will deliver the achievement of educational goals of Islam. Islamic education is basically the Democratization of space, the which is where the education is directed at a dialogical space. Moreover, the ultimate goal of Islamic education directs its final destination on the behavior and attitude changes, the quality and variety of aspects that promote humanism space. Islamic education should be oriented to instill democratic values in the learning process, such as openness, mutual respect, sympathy, empathy, solidarity, and their understanding of pluralism in a pluralistic life.